2007
DOI: 10.1007/s00192-007-0453-2
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas in diagnosing pelvic pain: multiple pelvic surgeries common in women with interstitial cystitis

Abstract: We determined the prevalence of pelvic surgeries in women with interstitial cystitis (IC) compared to community-based controls through responses to a survey from 215 women with IC and 823 controls. Women with IC had a statistically higher prevalence of hysterectomies (cases=42.3%, controls=21.4%), bladder suspensions (cases=21.9%, controls=5.7), pelvic or genital surgeries other than cystoscopy (cases=26.5%, controls=16.2%), and laparoscopic pelvic surgeries (cases=22.8%, controls=8.3%). Women with IC more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…11,18 Moreover, prior to being diagnosed with IC, these women often undergo multiple pelvic surgeries. 19 There are few reports of IC diagnosed in children and adolescents, 20e22 and this may be related to strict diagnostic criteria for IC research that exclude anyone younger than 18 years old. 16,22 Many women affected by IC had symptoms when they were younger, but it is not known if IC is a cause of CPP in young women.…”
Section: Introductionmentioning
confidence: 96%
“…11,18 Moreover, prior to being diagnosed with IC, these women often undergo multiple pelvic surgeries. 19 There are few reports of IC diagnosed in children and adolescents, 20e22 and this may be related to strict diagnostic criteria for IC research that exclude anyone younger than 18 years old. 16,22 Many women affected by IC had symptoms when they were younger, but it is not known if IC is a cause of CPP in young women.…”
Section: Introductionmentioning
confidence: 96%
“…The association of painful bladder syndrome and hysterectomy in our study is not entirely novel as women with interstitial cystitis are likely to have multiple pelvic surgeries 24 and women with interstitial cystitis may continue to have pelvic pain after a hysterectomy 25.…”
Section: Discussionmentioning
confidence: 80%
“…Our previous study showed that hysterectomy was a risk factor for IC/PBS in middle‐aged women . Other authors also found a higher rate of hysterectomy in IC/PBS patients . In contrast to hysterectomy, cesarean section is usually localized to the lower segment of the uterus.…”
Section: Discussionmentioning
confidence: 97%
“…The overall global cesarean section rate was 25.7% in 2010 . For years, many controlled studies have reported high incidence of patients with IC/PBS having a history of pelvic surgeries, including cesarean section . Pelvic surgeries may be risk factors for and even proximal triggers of IC/PBS, according to previous studies .…”
Section: Introductionmentioning
confidence: 99%